Analisis Rangkaian Pembagi Tegangan dan Perbandingan Hasil Simulasinya Menggunakan Simulator Offline - Syifaul Fuada; Maulida Yasmin; Meiliya Cahya Yustina; Annisa Amalia; Devi Anassafila Pratiwi; Amalia Annisa; Najwa Zahratul Kubro; Diar Dwi Sutia; Sahat Parulian; Muhammad Gani Baihaqi Darussalam; Ridha Febriliana; Yessi Tiyastanti; Rahadian Ilham Aji Rukmantara; Vina Fujiyanti; Gita Alisrobia Nazarudin (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
This paper reveals the voltage divider circuit to better understand the fundamental working principles in detail. The approach was simulated using popular offline simulators (i.e., Pr, CW circuit, and virtual mode, EWB, Mu, P, Ye, TS, QUCS, LTS, SI, and PhET). Two scenarios were carried out: measuring the output voltage (Vout) with known R1, R2, and DC source (Battery) as a voltage input (Vin), then looking for R1 and R2 using four different calculation methods to obtain Vout as expected. Afterward, the value of R1 and R2 were inserted into the simulation circuit to guarantee if the current Vout value matched the initial Vout. Finally, the simulation results were compared with the calculation results. All simulators provide an attractive GUI, capable of simulating voltage measurements with 100% accuracy in terms of DC analyses, which is DC voltage (except the CW software, which is only 98%), and can be entered in any resistor value (except Ye and PhET software). Surprisingly, the results of this study can provide insight for beginners to understand essential topics in electrical engineering studies, e.g., the circuit topology, fundamental theory, and working principle of a voltage divider circuit. Besides, the student will understand an offline electronic-based simulator suitable for measuring voltage parameters. Furthermore, they are expected to apply this circuit to various electronic circuit cases.